Hypertension induced by serotonin reuptake inhibitors: analysis of two pharmacovigilance databases - Humbert, Xavier; Fédrizzi, Sophie; Chrétien, Basile; Sassier, Marion; Bagheri, Haleh; Combret, Sandrine; Drici, Milou‐Daniel; Bas, François Le; Puddu, Paolo Emilio; Alexandre, Joachim (Fundamental and Clinical Pharmacology, 2018)
Abstract Drug‐induced hypertension was described with several pharmacological classes, especially with serotonin reuptake inhibitors (SRIs). However, this link has remained controversial: the French summary of product characteristics specify a risk of hypertension only with paroxetine and sertraline. To identify a possible class effect common to all SRIs, our study investigated the reports of hypertension associated with SRIs in two pharmacovigilance databases. Two different types of investigations were performed: (i) a comparative study in VigiBase®, which is the World Health Organization (WHO) pharmacovigilance database (PVDB), from where notifications of hypertension with six SRIs (citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine, sertraline) were extracted. The relationship between the suspected SRIs and the occurrence of hypertension was assessed by calculating reporting odds ratio (ROR) in a case/non‐case design; (ii) a descriptive study of hypertension reports associated with SRIs in the French pharmacovigilance database (FPVDB). In VigiBase®, 14 824 notifications of SRI‐induced hypertension (2.5%) were identified (mean age 54.3 years, mainly women 69.1%). Among them, 3 879 (26.2%) were associated to sertraline; 3 118 (21.0%) to fluoxetine; 2 725 (18.4%) to paroxetine; 2 570 (17.3%) to citalopram; 2 295 (15.5%) to escitalopram; and 237 (1.6%) to fluvoxamine. A significant ROR value was found with all six SRIs (ROR range from 1.16 to 1.92). In the FPVDB, 24 reports of hypertension were found with all six SRIs used at standard doses, mainly in women (66.7%) with a mean age of 57.8 years and a median time of onset of 6 days. In 10 cases (42%), patients had a history of hypertension. This study, performed in real conditions of life, shows a significant pharmacovigilance safety signal between the use of SRIs and the development or worsening of hypertension.